(untitled) (Conference Zone, 2022)
The article discusses the new content of the concept of "content of foreign language education", caused by changing objective processes in the world and in Europe; the most important documents and studies adopted by the Council of Europe in the field of foreign language education are presented, current trends in teaching foreign languages are indicated. The modern content of education is based on the principles of humanization, humanitarization, continuity, openness, diversification, virtuality, and focuses on anticipatory reflection of the problems of the development of society, production, science, culture, and other areas of social practice. The new content of education implies the continuity and multivariance of general and vocational education, which are based on fundamentalization and increased attention to the methodological component of education